2003
DOI: 10.1021/bi026395b
|View full text |Cite
|
Sign up to set email alerts
|

FeNO Structure in Distal Pocket Mutants of Myoglobin Based on Resonance Raman Spectroscopy

Abstract: /npsi/ctrl?action=rtdoc&an=12338206&lang=en http://nparc.cisti-icist.nrc-cnrc.gc.ca/npsi/ctrl?action=rtdoc&an=12338206&lang=fr READ THESE TERMS AND CONDITIONS CAREFULLY BEFORE USING THIS WEBSITE.http://nparc.cisti-icist.nrc-cnrc.gc.ca/npsi/jsp/nparc_cp.jsp?lang=en Vous avez des questions? Nous pouvons vous aider. Pour communiquer directement avec un auteur, consultez la première page de la revue dans laquelle son article a été publié afin de trouver ses coordonnées. Si vous n'arrivez pas à les repérer, communi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

14
111
0

Year Published

2004
2004
2018
2018

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 80 publications
(125 citation statements)
references
References 47 publications
14
111
0
Order By: Relevance
“…In ferric horse MbNO, an NO stretching band is found at 1927 cm Ϫ1 in the wild-type form and at 1904 cm Ϫ1 in the apolar mutant H64L (43). This observation shows that heme-bound NO has a similar sensitivity to its local environment as does CO (44). By analogy, we suggest that the two conformations of NP4 also differ in the polarity of the distal pocket, with the low pH A 1908 having a more hydrophobic distal pocket.…”
Section: Infrared Stretching Bands Of Heme-bound Ligands-mentioning
confidence: 64%
“…In ferric horse MbNO, an NO stretching band is found at 1927 cm Ϫ1 in the wild-type form and at 1904 cm Ϫ1 in the apolar mutant H64L (43). This observation shows that heme-bound NO has a similar sensitivity to its local environment as does CO (44). By analogy, we suggest that the two conformations of NP4 also differ in the polarity of the distal pocket, with the low pH A 1908 having a more hydrophobic distal pocket.…”
Section: Infrared Stretching Bands Of Heme-bound Ligands-mentioning
confidence: 64%
“…However, even with those obtained at high resolution, there is a significant range of FeNO conformations that suggest a role of distal residues in influencing FeNO geometry through a combination of factors including steric and electrostatic effects. This has been illustrated very well for Mb II NO [93][94][95], and related studies are ongoing for heme proteins in general, as distal and proximal effects are likely determinants of ligand discrimination and selectivity in heme-based sensor proteins. The role of cavity size in influencing FeNO bond angles has been demonstrated very well in the non-heme [(L)Fe(NO)] À anions (L = derivative of tris(N-R-carbamoylmethyl)amine), where the angle is 178.2(5)°when R = isopropyl, and 160.3(2)°when R = 3,5-dimethylphenyl [96].…”
Section: The Mb II No Structuresmentioning
confidence: 74%
“…From these observations, we concluded that OS-II has the heme iron directly coordinated by the N atom of butyraldoxime. Intriguingly, the 857-cm -1 vibrational frequency is much higher than the Fe-N single bond stretching frequency (500-600 cm -1 ) observed for the NO adducts of hemoproteins (41,42). Previously, Wagner and Nakamoto (43,44) reported a similar high Fe-N stretching frequency (876 cm -1 ) in the RR spectra of the photolysis products of the tetraphenylporphyrin azide complex, for which the formation of a perferryliron-N triple bond [Fe(V)ϵN] was proposed.…”
mentioning
confidence: 74%